Performance of wood joint from two selected timber species / Izharrashid Ghazali - Ghazali, Izharrashid (Faculty of Applied Sciences, 2016)
Nowadays, there are higher demands for furniture because many new housing units are built. Therefore, the addition of solid wood need to be critical, the way to overcome this is to use wood jointing for furniture. The wood jointing short pieces of lumber has become an increasingly popular method of reducing wood waste and utilizing shorts to realize maximum profit from bending properties of wood joint from two selected timber species (Endospermum Diadenum and Neolamarckia cadamba) by using finger joint, scarf joint and butt joint. The objective of this study is to determine mechanical (bending testing) of wood joints and to evaluate the effect of different wood species on wood joints properties. All the samples has been tested by bending properties (modulus of rupture and modulus of elasticity) conforming to the British Standard (BS EN 408:2010). The result showed that finger joint has the highest value, followed with scarf joint and the lowest are butt joint. Endospermum Diadenum performs better than Neolamarckia cadamba in wood joint but Neolamarckia cadamba is better in solid wood